2021
DOI: 10.1109/access.2021.3104903
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Instrumentation Control System Based on Low-Cost Single Board Computer Gateways

Abstract: Nowadays, most of the automatized measurement processes are carried out by VISA (Virtual Instrument Software Architecture) compatible instruments, that execute the instructions provided by a host computer connected through wired standard buses, as USB (Universal Serial Bus), GPIB (General-Purpose Instrumentation Bus), PXI (PCI eXtensions for Instrumentation) or Ethernet. To overcome the intrinsic limitations associated to these wired systems, this work presents an instrumentation control system based on the IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…A digital circuit of the transformation and transmission bridge was built and verified using two PCs and an FPGA development kit. The measured results present that the measured throughput, latency, and power consumption in this study are superior to those reported in [13,[16][17][18][19] and that only the Modbus TCP protocol is used in this study. Note that the proposed Ethernet and USB interface achieves the highest throughput (950.31 Mbps) and the lowest latency (18.845 µs).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…A digital circuit of the transformation and transmission bridge was built and verified using two PCs and an FPGA development kit. The measured results present that the measured throughput, latency, and power consumption in this study are superior to those reported in [13,[16][17][18][19] and that only the Modbus TCP protocol is used in this study. Note that the proposed Ethernet and USB interface achieves the highest throughput (950.31 Mbps) and the lowest latency (18.845 µs).…”
Section: Discussioncontrasting
confidence: 59%
“…Table 2 summarizes the measured specifications of the proposed Ethernet and USB bridge developed herein with FPGA (FPGA development kit)/PL (programmable logic) and compares them with those of previous studies. The performance comparison proved that the measured throughput, latency, and power consumption in this study are superior to those reported in [13,[16][17][18][19] and that only the Modbus TCP protocol is used in this study. The TCP/IP protocol is popular in [13,19] and this study.…”
Section: Simulation Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…SBC are also used when standard PCs are unsuitable [10]. The low power consumption of SBC also benefits wireless sensor networks and traditional data centers with up to 23x reduction in power consumption [11].…”
Section: The Evolution Of Quality Education: Impacts and Challenges O...mentioning
confidence: 99%